2017
DOI: 10.1007/s10453-017-9479-1
|View full text |Cite
|
Sign up to set email alerts
|

Modelled and observed surface soil pollen deposition distance curves for isolated trees of Carpinus betulus, Cedrus atlantica, Juglans nigra and Platanus acerifolia

Abstract: Modelled and observed surface soil pollen deposition distance curves for isolated trees of Carpinus betulus, Cedrus atlantica, Juglans nigra and Platanus acerifolia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…There is evidence that other factors may influence the relationship between pollen release and the abundance of cover in the vicinity of the sampler, including the size and maturity of individual trees, and the impact of environmental factors (e.g., wind) on pollen release and dispersal patterns [12,32]. Furthermore, although long-range transport of Platanus pollen is not very probable [56], potential long-range pollen transport between cities would be interesting to analyze in future studies [57].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that other factors may influence the relationship between pollen release and the abundance of cover in the vicinity of the sampler, including the size and maturity of individual trees, and the impact of environmental factors (e.g., wind) on pollen release and dispersal patterns [12,32]. Furthermore, although long-range transport of Platanus pollen is not very probable [56], potential long-range pollen transport between cities would be interesting to analyze in future studies [57].…”
Section: Discussionmentioning
confidence: 99%
“…Species belonging to these genera are frequently planted as ornamental plants in urban green zones. However, these anemophilous trees are also commonly found in forested areas surrounding Central European cities and as such it is likely that the majority of airborne pollen from these species recorded in Munich come from outside of the city [44,45]. It has also been shown that different levels of urbanization lead to differences in airborne pollen levels, with the lowest pollen concentrations generally registered in the most urban sites following an urban-rural gradient [42,46,47].…”
Section: Abundance Of the Pollen Types In The Airmentioning
confidence: 99%
“…However, Skjoth et al [58] stressed that individual trees could cause high concentrations of airborne pollen in areas that were hundreds of metres from the source. This result was confirmed by the high amount of pollen deposited within 100 m from a tree relative to that deposited at greater distances [63]. Maya-Manzano et al [26] assumed that the highest influence on olive, plane and cypress pollen concentrations in urban sites occurred within a distance of 500 m from the pollen monitoring site.…”
Section: Impacts Of Pollen Sources Vary In Spacementioning
confidence: 87%